A meta-analysis of the prognostic significance of CDKN deletions in acute lymphoblastic leukaemia - Xiaoshan Hu; Rui Xu; Sijian Yu; Qifa Liu (Annals of Medicine)
Background B-cell acute lymphoblastic leukaemia (B-ALL) and T-cell acute lymphoblastic leukaemia (T-ALL) are both types of acute lymphoblastic leukaemia (ALL), which is a cancer of the blood and bone marrow characterized by the rapid proliferation of immature lymphocytes. In ALL, CDKN gene deletions have been extensively studied regarding their prognostic significance. The purpose of this meta-analysis is to determine whether there is a consistent relationship between CDKN gene variations and the incidence of lymphocytic leukaemia.Materials and methods The following databases contain relevant studies published between inception and 25 October 2023: PubMed, EMBASE, the Cochrane library and Web of Science were comprehensively searched. Based on the random-effects or fixed-effects model, the hazard ratio (HR) and its 95% confidence interval (95% CI) were pooled. A subgroup analysis and sensitivity analysis were also conducted. We estimated publication bias using a funnel plot.Results This meta-analysis included 19 studies containing 1333 patients. Among included studies, 12 studies only reported B-ALL, four studies included patients with T-ALL and B-ALL, and three studies reported T-ALL. A deletion of the CDKN gene was found to be an adverse indicator of both EFS (HR = 1.83, 95% CI: 1.03–2.62), DFS (HR = 1.49, 95% CI 1.23–1.77), RFS (HR = 1.34, 95% CI 0.96–1.73) and OS (HR = 1.39, 95% CI 1.19–1.58). Single-arm emphasized the greater influence on OS. The subgroup analysis based on the CDKN2A, CDKN2A/b and different ALL subtypes further strengthen the validity of the findings.Conclusions Our meta-analysis revealed that CDKN gene deletions (including CDKN 2A/B, CDKN 2A) serve as adverse prognostic indicators for T-ALL/B-ALL patients.